Persians, a Long Thrēnos. - González-González, María Marta (Johns Hopkins University Press, 2022)
Starting from the idea that in Persians Aeschylus was attempting to arouse fear and pity in the audience (rather than glee at victory over the enemy), I propose to demonstrate that one of the resources he deployed to this end was the use of vocabulary and formulas typical of the genre of funerary epigraphy. This enabled him to present Persian grief in terms very familiar to the Athenian–and more generally, the Pan-Hellenic–audience. The influence of funerary epigraphy has not yet been analyzed in relation to Persians, but such an approach may shed new light on our understanding of this play.
Adjunta contrato de publicación que la autoriza a subir el artículo al repositorio de su institución.
Keywords: Esquilo - Crítica e interpretación; Epigramas griegos; Aeschylus; Persians; Funerary epigrams